Spreading the Gospel of Life - Napier, Wilfrid (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
To set out what the Church can and should do to live the Gospel of Life, in order to inspire and guide society to reverse the wanton disregard for the sacredness and value of human life.